Otroci s posebnimi potrebami v Sloveniji (1918-1990) - Dobaja, Dunja (Družboslovne razprave, 2022)
The article focuses on two groups of children with special needs: the deaf and hard of hearing, and the blind and visually impaired children. The article outlines the development of the education system for the mentioned groups of children in the period from the end of the First World War to the end of the socialist period at the start of the 1990s. The contribution mainly focuses on the period after the end of the Second World War. In that period, two underlying concepts were used in the care for children with special needs, namely segregation and integration
Keywords: 20. stoletje; Družbena integracija; gluhi; integracija; Ljubljana; otroci; Otroci s posebnimi potrebami; segragacija; Segregacija; slepi; socializem; socialna politika; socialno delo